Imagining the preventive city: How can urban environments support dementia prevention? A qualitative study. (31st December 2021) - Roehr, Susanne; Rodriguez, Francisca S; Siemensmeyer, Rosa; Mueller, Felix; Romero‐Ortuno, Roman; Riedel‐Heller, Steffi G
Abstract: Background: Interventions for the risk reduction of cognitive decline and dementia are currently largely focused on individual‐level strategies. To maximize risk reduction, it is useful to consider how the environment we live in can support dementia prevention, i.e. promote healthy lifestyle behaviors known to attenuate dementia risk. As the majority of the ageing population will be living in cities in the future, we specifically explored how dementia prevention could be addressed in urban environments with the aim of generating transformative ideas for public health policy. Method: In our trans‐ and multidisciplinary qualitative study, we conducted in‐depth problem‐centered, semi‐structured interviews with 10 community‐dwelling individuals at least 65 years of age and 10 experts (fields covered: architecture, cultural/arts education, environmental sciences, geriatrics, health policy, IT, philosophy, psychology, public health, and urban sociology), all living in the city of Leipzig, Germany. Interview guides were informed by the framework on modifiable risk factors for dementia of the Lancet Commission on Dementia Prevention, Intervention, and Care. Interviews were audio‐recorded and verbatim transcribed. Data were categorized and coded using computer‐assisted content analysis. Result: Community‐dwelling individuals were M = 73.7 ( SD = 6.0) years old, 50% were women. Experts were aged 39 to 72 years, 70% were women. Across interviews, both older individuals and experts stressed three urban environmental aspects to promote dementia prevention in the city: social participation and inclusion (emphasizing intergenerationality, digital literacy, co‐creating, cultural/arts/community events and lifelong learning), proximity and accessibility (emphasizing neighborhoods, social housing, mobility, access to health care services, public toilets) and local recreation (emphasizing urban greenery, environmental protection, public gardening, outdoor physical activity, cleanliness and security, especially after dark). Conclusion: Urban environments play a crucial, but yet too little recognized role for promoting comprehensive healthy lifestyle behaviors that attenuate dementia risk. Public policy should more involve older community members in defining and creating such environments. Moreover, urban environments that promote healthy lifestyle behaviors may be particularly beneficial for marginalized and deprived community groups, which are usually hard to reach by individual‐level interventions.